A Rainfall Simulator Used for Testing of Hydrological Performances of Micro-Detention Permeable Pavement - Bateni, Norazlina; Hin Lai, Sai; Josep Putuhena, Frederik; Yau Seng Mah, Darrien; Abdul Mannan, Md (International Journal of Engineering and Technology, 2018)
A rainfall simulator for laboratory experimentation is developed to test hydrological performances of micro-detention pond permeable pavement, MDPP. Rainfall characteristics consisting of rainfall intensity, spatial uniformity, raindrop size, and raindrop velocity show that natural rainfall is simulated with sufficient accuracy. The rainfall simulator used pressure nozzles to spray water for rainfall intensity from 40 to 220mm/hr. Uniformity distribution test gives coefficient of uniformity of 95% over an area of 1m2. The raindrops falling at velocity ranging from 0.5 to 15m/s with drop sizes diameter between 2 to 5mm. Free drainage system below the rainfall simulator is accompanied with outlet tanks attached with ultrasonic sensor devices to record the outflow data. During the experiments, the outflow received is 98% in average. Experiment results in typical runoff hydrograph and percolation rate of the MDPP system. This shows the ability of the rainfall simulator to obtain initial hydrology data to aid in the design of the MDPP prototype.Â Â